An Analysis of Factors Contributing to Low Interest in Denture Use Among the Elderly in Denpasar City: A Hanlon Theory Approach - Ni Putu Idaryati; I Gusti Agung Ayu Chandra Iswari Dewi; Gusti Ayu Yohanna Lily; I Nyoman Panji Triadnya Palgunadi; Yudha Rahina; I Gusti Ayu Ari Agung; I Wayan Agus Wirya Pratama; I Gusti Ayu Ratih Pramesti (Interdental Jurnal Kedokteran Gigi (IJKG), 2025)
Introduction: The increasing life expectancy in Indonesia, including  Denpasar City, has led to a growing elderly population. Older adults are vulnerable to various health problems, including tooth loss. This condition can impair chewing function, affect facial aesthetics, and ultimately reduce the quality of life. Dentures are a commonly used solution; however, their use among the elderly remains low. Therefore, it is important to explore the factors influencing the interest in using dentures. Material and Methods: This study was a qualitative research including a descriptive exploratory approach. Data were collected through in-depth interviews with 20 older adults from five community units (banjar) in Denpasar City, selected purposively. Data were analyzed thematically using the Hanlon method, which considers the magnitude of the problem,  seriousness of the impact,  effectiveness of the solution, and feasibility of implementation, to assess and prioritize the factors contributing to the low interest in denture use. Results and Discussions: Six main themes were identified as influencing the low interest in denture use: passive acceptance of tooth loss as a natural part of aging, limited access due to lack of transportation or assistance, (3) low knowledge about the benefits of dentures, discomfort during use, perception of high costs, and ignorance of the Indonesian health insurance coverage. Conclusion: The low interest in denture use among older adults is influenced by psychosocial, structural, and educational factors. Educational interventions, provision of mobile health services, and culturally sensitive, community-based approaches are needed to improve denture utilization among older adults.